Ovarian tumor pathology in adolescents - Pantoja, Celia (2015)
OBJECTIVE: To determine the profile of presentation of the ovarian tumor pathology in adolescent women. DESIGN: Retrospective and descriptive study. MATERIALS AND METHODS: The medical records and reports of ovarian tissue biopsy of 48 adolescents aged 10 to 19 years hospitalized in the Gynecology Service of the National Hospital Cayetano Heredia age, between July 1992 and December 1998. We excluded revised pregnant teenagers more than 20 weeks gestation. RESULTS: The most common findings were serous cystadenoma (45.6%), dermoid cyst (20.8%), corpus luteum (8.3%), functional ovarian cyst (6.3%), ovarian cistoadenofibroma (6, 3%), dysgerminoma (4.2%), mucinous cystadenoma (4.27%) and mixed cystadenoma (2.1%). CONCLUSIONS: Benign ovarian tumor pathology (37casos, 77%) is more common than malignant (4 cases, 8.3%) in adolescents. The presentation profile of ovarian tumor pathology of adolescents in our environment is similar to that published in Peru and abroad.